EFEKTIVITAS EKSTRAK BAWANG PUTIH (Allium sativum) UNTUK MENCEGAH DAN MENGOBATI MOTILE AEROMONAS SEPTICEMIA (MAS) PADA IKAN MAS (Cyprinus carpio) - Iesje Lukistyowati; Windarti Windarti; Morina Morina; Alim Isnansetyo; Kurniasih Kurniasih (Universitas Gadjah Mada, 2008)
The aim of study was to know the effectiveness of garlic (Allium sativum) extract in preventing and curing Motile Aeromonas Septicemia (MAS) in common carp (Cyprinus carpio). Garlic extract was obtained by juicing fresh garlic and filtering by using filter paper. Common carp (8-12 cm in total lenght) were used. Infection was done by injecting intraperitonially 0.1 ml 0f 24 h Aeromonas hydrophila culture at bacterial density of 108 cells/ml. Garlic extract was given by immersing the fish at various concentrations. Results indicated that the minimum inhibitory concentration (MIC) of the garlic extract againtst A. hydrophila ranged from 61.300-125.000 ppm, while the LD50 of this extract was 3.438 ppm. The use of garlic extract to prevent MAS was effective as survival rate of the treated fish with the extract at 1000, 2000, and 3000 ppm ranged from 83 to 100% while the survival rate of untreated fish was 60.71%. However, the use of garlic extract to cure MAS was not effective as the survival rate of the treated fish ranged 50-80% which were the same or even lower than that of the control (76.67%).